The use of biphasic calcium sulfate (Bond Apatite®) for surgical treatment of osseous defects resulting from radicular cysts - Clinical study of 6 months follow-up - Dudek Damian; Reichmann- Warmusz Edyta; Kurtzman M Gregori; Mahesh Lanka (Wolters Kluwer Medknow Publications, 2020)
Surgical treatment of odontogenic cysts of the jaws accounts for a significant percentage of dental surgery procedures. Additionally, a wide range of procedures and augmentation materials are used in the reconstruction of these osseous defects. The authors present a study including histology of surgical treatment of odontogenic cysts using a Biphasic Calcium Sulfate composite bone graft cement (Bond Apatite®).